SOSIALISASI DAN PELATIHAN KEAMANAN INTERNET DAN PENGAMANAN INFORMASI DATA PRIBADI BAGI SISWA-SISWI SMA UNTUNG SUROPATI SIDOARJO - Rizky Basatha; Alexander Wirapraja; Raymond Sutjiadi; Edwin Meinardi Trianto; Eddy Triswanto Setyoadi (LPPM Universitas Bina Bangsa, 2023)
Every data and information circulating on the internet is open and easily accessible by anyone, awareness of the importance of securing data and information is still a major concern. Data and information cannot be erased easily and can sometimes become digital footprints that can be detrimental to users. This community service program takes the theme of internet security by targeting youth who still have limitations in understanding and knowing the dangers of freely sharing personal data and information on the internet. The method of implementing this activity is to provide seminars and discussions as well as presentation of examples related to internet security. The result of this activity is that students from community service partners become aware of the potential dangers related to internet security